On Multiple Hall‐Like Electron Currents and Tripolar Guide Magnetic Field Perturbations During Kelvin‐Helmholtz Waves. Issue 2 (23rd February 2018) - Sturner, Andrew P.; Eriksson, Stefan; Nakamura, Takuma; Gershman, Daniel J.; Plaschke, Ferdinand; Ergun, Robert E.; Wilder, Frederick D.; Giles, Barbara; Pollock, Craig; Paterson, William R.; Strangeway, Robert J.; Baumjohann, Wolfgang; et al.
Abstract: Two magnetopause current sheet crossings with tripolar guide magnetic field signatures were observed by multiple Magnetosphere Multiscale (MMS) spacecraft during Kelvin‐Helmholtz wave activity. The two out‐of‐plane magnetic field depressions of the tripolar guide magnetic field are largely supported by the observed in‐plane electron currents, which are reminiscent of two clockwise Hall current loop systems. A comparison with a three‐dimensional kinetic simulation of Kelvin‐Helmholtz waves and vortex‐induced reconnection suggests that MMS likely encountered the two Hall magnetic field depressions on either side of a magnetic reconnection X‐line. Moreover, MMS observed an out‐of‐plane current reversal and a corresponding in‐plane magnetic field rotation at the center of one of the current sheets, suggesting the presence of two adjacent flux ropes. The region inside one of the ion‐scale flux ropes was characterized by an observed decrease of the total magnetic field, a strong axial current, and significant enhancements of electron density and parallel electron temperature. The flux rope boundary was characterized by currents opposite this axial current, strong in‐plane and converging electric fields, parallel electric fields, and weak electron‐frame Joule dissipation. These return current region observations may reflect a need to support the axial current rather than representing local reconnection signatures in the absence of any exhausts. Plain Language Summary: Simulations suggest that, under certain conditions, waves can form along the boundary of the Earth's magnetic field. Sometimes, the magnetic fields can rapidly change shape and connect across the boundary, possibly even multiple times within half a wavelength. We analyzed variations in the magnetic field and currents at this boundary using NASA's MMS satellites and find evidence suggesting multiple reconnection points. We also compare the spacecraft observations to a simulation of this event and believe we might be encountering rope‐like structures that can form through multiple reconnection. Key Points: MMS observed the first KH‐associated tripolarB M guide‐field supported by in‐plane Hall‐like electron current loops TripolarB M observations were reproduced by Hall‐like current loops in a 3D PIC simulation of vortex‐induced driven reconnection MMS observations near a significantB N deflection within aB L  ~ 0 plateau of one current sheet are consistent with a narrow flux rope with strong axial current